The interdependence of major European stock markets: evidence for Greece - Καινούργιος, Δημήτριος Φ.; Σαμίτας, Αριστείδης Γ. (SPOUDAI Journal of Economics and Business, 2003)
This paper provides new evidence on the relationship between the Greek "blue chip" stock market and the six relative European markets by applying cointegration tests. The time period examined is 1998 to 2000, which marks the entry of Greece to the European Exchange Rates Mechanism II. The empirical results indicate that the Athens Stock Exchange has no considerable links, except for one case, with any other European developed markets examined. These findings have some significant implications for European-oriented portfolio diversification and the national stock market integration hypothesis. JEL Classification: C12, C32, G14